PANTASKAH ORANG BERIMAN MENDERITA? (Sebuah Refleksi Teologis tentang Penderitaan Ayub) - Benedictus Hasan (Aggiornamento, 2021)
The author places the focus of this paper on an elaboration of the suffering that Job experienced. Job was a pious person who always obeyed and feared God, but as a believer, he seemed to be inseparable from suffering. Suffering is a reality that is always experienced by humans. The problem is how to view suffering in the perspective of a believer's life. This elaboration is within the broad outline of the entire book of Job in union with the rest of Scripture. Then this elaboration will be directed to the meaning of suffering experienced by humans "today". The method of writing is literature study by reading interpretation books, as well as articles related to this theme. The findings of this paper ultimately lead to the conclusion that God is He who is sovereign. Because of His sovereignty, He has power over all of His creations, including humans. God's sovereignty cannot be understood in a negative, arbitrary manner. All of God's actions, including the suffering experienced by humans, seem to lead to His glory. Thus, humans are always directed to the glory of God.